Prevalence and determinants of symptoms related to mental disorders in retired male professional footballers - Gouttebarge, V.; Aoki, H.; Kerkhoffs, G. M. (The Journal of Sports Medicine and Physical Fitness, 2016)
OBJECTIVE: The objective of this study was to determine the prevalence of symptoms related to mental disorders (distress, anxiety/depression, sleep disturbance, adverse alcohol behaviour, adverse smoking behaviour, adverse nutrition behaviour) among retired professional footballers, and to explore their associations with stressors i.e. determinants such as severe injury, surgery, life events and career dissatisfaction.